Learning deficit in cognitively normal APOE ε4 carriers with LOW β‐amyloid. Issue 1 (16th March 2021) - Lim, Yen Ying; Baker, Jenalle E.; Mills, Andrea; Bruns, Loren; Fowler, Christopher; Fripp, Jurgen; Rainey‐Smith, Stephanie R.; Ames, David; Masters, Colin L; Maruff, Paul
Abstract: Introduction: In cognitively normal (CN) adults, increased rates of amyloid beta (Aβ) accumulation can be detected in low Aβ (Aβ–) apolipoprotein E ( APOE ) ε4 carriers. We aimed to determine the effect of ε4 on the ability to benefit from experience (ie, learn) in Aβ– CNs. Methods: Aβ– CNs (n = 333) underwent episodic memory assessments every 18 months for 108 months. A subset (n = 48) completed the Online Repeatable Cognitive Assessment‐Language Learning Test (ORCA‐LLT) over 6 days. Results: Aβ– ε4 carriers showed significantly lower rates of improvement on episodic memory over 108 months compared to non‐carriers (d = 0.3). Rates of learning on the ORCA‐LLT were significantly slower in Aβ– ε4 carriers compared to non‐carriers (d = 1.2). Discussion: In Aβ– CNs, ε4 is associated with a reduced ability to benefit from experience. This manifested as reduced practice effects (small to moderate in magnitude) over 108 months on the episodic memory composite, and a learning deficit (large in magnitude) over 6 days on the ORCA‐LLT. Alzheimer's disease (AD)–related cognitive abnormalities can manifest before preclinical AD thresholds.